Good learning environment of medical schools is an independent predictor for medical students’ study engagement - Huang, Runzhi; Li, Yuanan; Gong, Meiqiong; Zhang, Wei; Xian, Shuyuan; Tang, Jieling; Lu, Bingnan; Yang, Yiting; Jin, Minghao; Qian, Weijin; Liu, Zhenglin; Ma, Haonan; et al. (Frontiers in Medicine, 2024)
Background Study engagement is regarded important to medical students' physical and mental wellbeing. However, the relationship between learning environment of medical schools and the study engagement of medical students was still unclear. This study was aimed to ascertain the positive effect of learning environment in study engagement.We collected 10,901 valid questionnaires from 12 medical universities in China, and UWES-S was utilized to assess the study engagement levels. Then Pearson Chi-Square test and Welch's ANOVA test were conducted to find the relationship between study engagement and learning environment, and subgroup analysis was used to eradicate possible influence of confounding factors. After that, a multivariate analysis was performed to prove learning environment was an independent factor, and we constructed a nomogram as a predictive model.Result With Pearson Chi-Square test (p < 0.001) and Welch's ANOVA test (p < 0.001), it proved that a good learning environment contributed to a higher mean of UWES scores. Subgroup analysis also showed statistical significance (p < 0.001). In the multivariate analysis, we could find that, taking 'Good' as reference, 'Excellent' (OR = 0.329, 95%CI = 0.295-0.366, p < 0.001) learning environment was conducive to one's study engagement, while 'Common' (OR = 2.206, 95%CI = 1.989-2.446, p < 0.001),' 'Bad' (OR = 2.349, 95%CI = 1.597-3.454, p < 0.001) and 'Terrible' (OR = 1.696, 95%CI = 1.015-2.834, p = 0.044) learning environment only resulted into relatively bad study engagement. Depending on the result, a nomogram was drawn, which had predictive discrimination and accuracy (AUC = 0.680).We concluded that learning environment of school was an independent factor of medical student's study engagement. A higher level of learning environment of medical school came with a higher level of medical students' study engagement. The nomogram could serve as a predictive reference for the educators and researchers.